2020
DOI: 10.1021/acscatal.9b05011
|View full text |Cite
|
Sign up to set email alerts
|

α-Amino Radicals via Photocatalytic Single-Electron Reduction of Imine Derivatives

Abstract: The construction and manipulation of amine-containing architectures is of importance to academic and industrial development and discovery programs. The photochemical single-electron reduction of imine derivatives to generate α-amino radical intermediates has emerged as a powerful umpolung strategy for opening up underexplored routes to such amine motifs. Furthermore, these radicals have been shown to engage in a wide variety of chemistry, including radical–radical coupling, addition to electrophiles, and reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(92 citation statements)
references
References 113 publications
1
82
0
Order By: Relevance
“…This result can explain the necessity of a higher loading of the photocatalyst (3.5 mol %) in our optimized conditions. Indeed, the presence of free imine, in constant equilibrium with iminium ion, can be involved in the reductive quenching of the photocatalyst ( Leitch et al., 2020 ). An experiment of radical trapping via TEMPO confirmed the formation of alkyl (R) radical (detected by GC-MS) from BA precursor ( Scheme S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…This result can explain the necessity of a higher loading of the photocatalyst (3.5 mol %) in our optimized conditions. Indeed, the presence of free imine, in constant equilibrium with iminium ion, can be involved in the reductive quenching of the photocatalyst ( Leitch et al., 2020 ). An experiment of radical trapping via TEMPO confirmed the formation of alkyl (R) radical (detected by GC-MS) from BA precursor ( Scheme S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…From a mechanistic standpoint, and in order to elucidate the origin of the reagent‐controlled diastereodivergent photocatalytic cyclisation, in‐depth DFT (density functional theory) analysis (see Supporting Information for full computational details) was performed (Scheme 6 ). The α‐amino radical 1 , generated by the well‐established iridium photocatalyst mediated proton‐coupled electron transfer (PCET) of imine 1 b ,[ 1a , 5a , 7 , 8 ] undergoes the first cyclisation through Giese addition to the tethered α,β‐unsaturated ester (Scheme 6 A ). [ 5c , 22 ] Studies on the first cyclisation revealed that the formation of trans intermediate 2‐ trans through the transition structure (TS) TS2 is kinetically favoured in comparison to TS1 that forms 2‐ cis .…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is clearly illustrated (Scheme 2) by the formation of -amino radicals from either alkylamines by oxidation (reductive quenching of the photocatalyst) 10 or from imino compounds by reduction (oxidative quenching of the photocatalyst). 11 Alkylamines and imino compounds are readily available and conveniently handled. Furthermore, -amino acids can serve as surrogates for alkylamines in such transformations, as the carboxylate group is a handle for decarboxylation to also furnish -amino radicals.…”
Section: Introductionmentioning
confidence: 99%